An Evaluation Framework for New ICTs Adoption in Architectural Education - Franklyn Chukwunonso; Michael. C Oguike (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
The  advent  of  new  Information  and  Communication Technologies (ICTs) poses several challenges for its use and adoption particularly for teaching and learning   purposes   in most   Higher   Educational  Institutions (HEIs). Understanding the criteria to use and how to measure success are some of the challenges   faces   by   most departments   of   Architecture   in   Nigerian Universities. Thus,  this  paper  has  attempted to  address  these challenges  by proposing an evaluation framework for the adoption of new ICTs in tertiary institutions  of  learning  with particular interest  in  Architectural  education. Baseline information  collected  from the  department  of  architecture in  five different  Nigerian  Universities was  used  to  identify the  major  constraints encountered  in  Information and Communication  Technologies  adoption  in Architectural education and the best approach that will promote better rate of Information Technology (IT) adoption. The major contribution of the study is that  the  proposed framework can  be  used  to  interpret  specific  results  as  to whether the use  of  technology  within  a  particular  literacy  program led  to improved learning,  and  provide  a  better understanding  of  such  results  in larger contexts  and various  aspects  of  other  issues  related  to evaluation, access, and literacy learning in Architectural education.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.5285